THE ROLE OF MASS SPORTS IN PROMOTING A HEALTHY LIFESTYLE IN MODERN SOCIETY - Akmal Tojiddinovich Kholiqov; Nurlan Kydyrbekovich Yerepbayev (World Scientific Research Journal, 2025)
Annotation: This article explores the crucial role of mass sports in developing a healthy lifestyle in today’s rapidly changing world. It highlights the impact of physical activity on public health, the socio-economic importance of sports participation, and examines policies and initiatives, particularly in Uzbekistan, that promote mass sports as a means to foster physical and mental well-being across all age groups.